Gas tungsten arc welding of as-rolled CrMnFeCoNi high entropy alloy. (April 2020) - Oliveira, J.P.; Curado, T.M.; Zeng, Z.; Lopes, J.G.; Rossinyol, Emma; Park, Jeong Min; Schell, N.; Braz Fernandes, F.M.; Kim, Hyoung Seop
Abstract: High entropy alloys have emerged as novel engineering alloys with remarkable mechanical properties in a wide range of temperatures. Among the several high entropy alloys that were already described, the equiatomic CrMnFeCoNi alloy is the most studied one. In this work, gas tungsten arc welding of as-rolled CrMnFeCoNi high entropy alloy sheets was performed. The microstructural characterization encompassed the use of electron microscopy, including electron backscattered diffraction, synchrotron X-ray diffraction analysis, microhardness testing and mechanical evaluation. A comprehensive description of the microstructural evolution, including texture and microstrain determination, of the joint is presented and discussed. Upon mechanical testing, the joints systematically failed in the fusion zone due. The large grain size and low hardness of this region justifies the failure location. The joints' mechanical behaviour is correlated with the material microstructure. Graphical abstract: Unlabelled Image Highlights: Gas tungsten arc welding of as-rolled CrMnFeCoNi high entropy alloys is performed. Defect-free joints with good mechanical behaviour were obtained. Synchrotron X-ray diffraction was used to study the texture and microstrain along the joint. Arc-based welding techniques are suitable for welding these novel advanced engineering alloys.